2007
DOI: 10.1091/mbc.e07-03-0239
|View full text |Cite
|
Sign up to set email alerts
|

STAM and Hrs Down-Regulate Ciliary TRP Receptors

Abstract: Cilia are endowed with membrane receptors, channels, and signaling components whose localization and function must be tightly controlled. In primary cilia of mammalian kidney epithelia and sensory cilia of Caenorhabditis elegans neurons, polycystin-1 (PC1) and transient receptor polycystin-2 channel (TRPP2 or PC2), function together as a mechanosensory receptor-channel complex. Despite the importance of the polycystins in sensory transduction, the mechanisms that regulate polycystin activity and localization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
74
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(87 citation statements)
references
References 98 publications
11
74
1
Order By: Relevance
“…Tubby proteins may also regulate endocytosis of signaling proteins (Mukhopadhyay et al 2005(Mukhopadhyay et al , 2007aChen et al 2012). We and others previously showed that defects in endocytosis result in ciliary protein localization defects as well as characteristic ciliary morphological defects (Hu et al 2007;Kaplan et al 2012). Although phenotypes in tub-1 mutants are not identical to those in endocytic mutants, we cannot exclude the possibility that the GPCR mislocalization phenotypes in tub-1 mutants arise from defects in endocytosis.…”
Section: Discussionmentioning
confidence: 72%
“…Tubby proteins may also regulate endocytosis of signaling proteins (Mukhopadhyay et al 2005(Mukhopadhyay et al , 2007aChen et al 2012). We and others previously showed that defects in endocytosis result in ciliary protein localization defects as well as characteristic ciliary morphological defects (Hu et al 2007;Kaplan et al 2012). Although phenotypes in tub-1 mutants are not identical to those in endocytic mutants, we cannot exclude the possibility that the GPCR mislocalization phenotypes in tub-1 mutants arise from defects in endocytosis.…”
Section: Discussionmentioning
confidence: 72%
“…A number of proteins involved in the exocytic delivery of cilia membrane and protein components have been described, including the BBSome complex and the Rab8 small GTPase (Deretic et al, 1995;Jin et al, 2010;Moritz et al, 2001;Nachury et al, 2007). Although the BBSome has been implicated in ciliary protein removal (Lechtreck et al, 2009), we and others have shown that active clathrin-mediated endocytosis also plays an important role in the retrieval of ciliary membrane and maintenance of cilia morphology (Hu et al, 2007;Kaplan et al, 2012). Thus, ciliary structural and functional homeostasis is likely to be maintained in part via a balance between exocytosis and endocytosis, suggesting that the precise regulation of these pathways is crucial for ciliary morphogenesis.…”
Section: Introductionmentioning
confidence: 84%
“…[74][75][76][77] Based on the structural information available and existing sequence homology among other TRPs, especially with TRPV members and the manner by which the surface expression of TRP channels are regulated, it can be speculated that proteins like Signal Transducing Adaptor Molecule (STAM), Hrs (which downregulate TRPP2 in C. elegans) and Recombinase Gene Activator (RGA, which regulates cell surface expression of TRPV2) may also be involved in the surface expression of TRPV4. [78][79][80] However, further detailed studies are needed to confirm if these proteins really interact and are involved in the surface expression of TRPV4.…”
mentioning
confidence: 99%